2019
DOI: 10.1101/584714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Arrival of Steppe and Iranian Related Ancestry in the Islands of the Western Mediterranean

Abstract: 53 54 55 56 57 58 A series of studies have documented how Steppe pastoralist-related ancestry reached central 59 Europe by at least 2500 BCE, while Iranian farmer-related ancestry was present in Aegean 60Europe by at least 1900 BCE. However, the spread of these ancestries into the western 61 Mediterranean where they have contributed to many populations living today remains poorly 62 understood. We generated genome-wide ancient DNA from the Balearic Islands, Sicily, and 63 Sardinia, increasing the number of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Therefore, it cannot be excluded, that these females also originate from regions further south since also some regions e.g., Italy are not genetically described so far for this particular time span. However, individuals without any steppe-related ancestry can be found up until 2479-1945 BCE for example in Iberia or until 2900-1700 BCE in the Minoan population of Crete 21,36 and even later on Sardinia where steppe-related ancestry arrives around 300 CE 37 and where studies of present-day Sardinians found indications of continuity in mountainous regions since Neolithic times 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it cannot be excluded, that these females also originate from regions further south since also some regions e.g., Italy are not genetically described so far for this particular time span. However, individuals without any steppe-related ancestry can be found up until 2479-1945 BCE for example in Iberia or until 2900-1700 BCE in the Minoan population of Crete 21,36 and even later on Sardinia where steppe-related ancestry arrives around 300 CE 37 and where studies of present-day Sardinians found indications of continuity in mountainous regions since Neolithic times 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The data also link Sardinia from the Iron Age onwards to the broader Mediterranean in what seems to have been a period of new dynamic contact throughout much of the Mediterranean. A parallel study focusing on islands of the western Mediterranean provides generally consistent results and both studies make clear the need to add complexity to simple models of sustained isolation that have dominated the genetic literature on Sardinia 52 . Finally, our results suggest some of the current substructure seen on the island (e.g., Ogliastra) has emerged due to recent genetic drift.…”
Section: S S Se Se S S a A A A A A A A E Se E E E E E E E E E Se S A Amentioning
confidence: 56%
“…Using qpAdm, we modeled the genetic shift by an introduction of ~30 to 40% ancestry from Bronze and Iron Age nomadic populations from the Pontic-Caspian Steppe (table S15), similar to many Bronze Age populations in Europe (10,13,14,19,22). The presence of Steppe-related ancestry in Iron Age Italy could have happened through genetic exchange with intermediary populations (5,23). Additionally, multiple source populations could have contributed, simultaneously or subsequently, to the ancestry transition before Iron Age.…”
Section: The Iron Age and The Origins Of Romementioning
confidence: 99%